Large Dumbbell-Shaped C1 Schwannoma Presenting as a Foramen Magnum Mass - Helms, Jody; Michael, Lattimore Madison, II (Journal of Neurological Surgery Reports, 2012)
Schwannomas involving the foramen magnum commonly originate from the lower cranial nerves, but they are rarely found arising from the first cervical root. To date, very few cases have been described in the literature. The majority involve either the intradural or extradural compartment but not both. We report the second case of a dumbbell-shaped schwannoma arising from the first cervical root. Our patient presented with hemisensory deficits secondary to brainstem compression at the level of the foramen magnum. The patient underwent a far lateral approach, and a gross total resection was achieved. Preoperative suspicion of the diagnosis is helpful in anticipating displacement and avoiding damage to the surrounding neurovascular structures.
Keywords: schwannoma; C1; first cervical nerve root; dumbbell shape; foramen magnum mass